2021
DOI: 10.1002/uog.23631
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and potential harms of COVID‐19 vaccination during pregnancy: evidence summary for patient counseling

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…At present, data on the safety and efficacy of COVID-19 vaccination in pregnancy are limited owing to the exclusion of pregnant women in clinical trials, 34 although trials are now underway to address this urgent need. This has motivated widespread hesitancy about recommendation of vaccination to all pregnant women, with governments and professional organizations initially recommending offering vaccination to pregnant women at high risk of either occupational exposure or severe disease 35 and pregnant women reluctant to take up a vaccine offer. 36 In the United States and Israel, where vaccination has been recommended to those at a higher risk, initial data provide a positive signal of safety and efficacy in pregnant women.…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
“…At present, data on the safety and efficacy of COVID-19 vaccination in pregnancy are limited owing to the exclusion of pregnant women in clinical trials, 34 although trials are now underway to address this urgent need. This has motivated widespread hesitancy about recommendation of vaccination to all pregnant women, with governments and professional organizations initially recommending offering vaccination to pregnant women at high risk of either occupational exposure or severe disease 35 and pregnant women reluctant to take up a vaccine offer. 36 In the United States and Israel, where vaccination has been recommended to those at a higher risk, initial data provide a positive signal of safety and efficacy in pregnant women.…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
“…2 Theoretically, COVID-19 vaccines are safe for use in pregnancy, as they do not contain a live attenuated virus. 3 For COVID-19 vaccination in pregnancy, there has been no major safety signal from animal reproductive toxicology studies, the very small number of inadvertent pregnancies in vaccine trials, the Centers for Disease Control and Prevention (CDC) V-safe postvaccination health checker (with limited data on >30,000 pregnant women, but only 827 women have given birth), or a formal pregnancy registry (>1800 enrolled to date). 4 A recent report of American health workers who were pregnant (n¼84) or lactating (n¼31) when vaccinated found that compared with nonpregnant controls (n¼16), vaccine-induced humoral immunity was similar, antibody titers were higher following an actual SARS-CoV-2 infection, and antibodies were present in umbilical cord blood and breast milk, suggesting that vaccination can confer maternal and perinatal immunity.…”
Section: Introductionmentioning
confidence: 99%
“…These spike proteins are expressed on the cellular surface, triggering the activation of cell-mediated and humoral immune systems and the creation of B memory cells which produce SARS-CoV-2-spike protein specific antibodies. The vaccine mRNA does not enter the nucleus or change host DNA, 63 are replication-deficient and have short lifespan characteristics, thus the likelihood of transplacental transfer of mRNA vaccine active compounds is low. 57,64,65 Pfizer-BioNTech's BNT162b2's Phase 3 clinical trial data reports side-effects such as local injection-site reactions (66%-88%), and mild to moderate systemic events including fever, fatigue, headache, and musculoskeletal pain (less than 60%).…”
Section: Covid-19 Vaccinesmentioning
confidence: 99%
“…These spike proteins are expressed on the cellular surface, triggering the activation of cell‐mediated and humoral immune systems and the creation of B memory cells which produce SARS‐CoV‐2‐spike protein specific antibodies. The vaccine mRNA does not enter the nucleus or change host DNA, 63 are replication‐deficient and have short lifespan characteristics, thus the likelihood of transplacental transfer of mRNA vaccine active compounds is low. 57 , 64 , 65…”
Section: Covid‐19 Vaccinesmentioning
confidence: 99%